Automatization of estimation of aviation personnel psychophysiological condition in operation regime - Занько, С. Н. (Proceedings of National Aviation University (archive), 2000)
Human condition is characterized in general by multifactor criteria, the change of most of them requires special measuring devices and considerable research time. In operating conditions such research, as a rule, can be carried out only in exceptional cases. Thus it is actual to estimate psychophysiological condition of a man with application of modern computer-information technologies